PENGARUH KONFLIK PERAN, KETIDAKJELASAN PERAN, DAN SESNSITIVITAS ETIKA PROFESI TERHADAP KINERJA AUDITOR DENGAN KECERDASAN EMOSIONAL SEBAGAI VARIABEL MODERATING - Susanti, Mulyani; Hasan, Amir; ', Al Azhar A (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study the influence of role conflict, role ambiguity, sensitivity of profesional ethics to auditors performance with emotional quotient as moderating variabele. Respondents in this study are the auditors who work in public accounting firm in Pekanbaru, Padang, Batam. The number of auditors that were visited in this study were 95 respondents. The method of sample is by using Quota sampling method.while the data processing methods used by researcher are the multiple regresion and moderating regression analysis. The result shows that: 1) Role conflict influence significanly to auditors performance, whith significanly value 0.000 < 0.05. 2) role ambiguty influence negatively and significanly to auditors performace, with significanly value 0.627 > 0.05. 3) sensitivity of professional ethics influence significanly to auditors performance, with significanly value 0.627 > 0.05. emotional quotient is a moderating variable between influence of role conflict, sensitivity of professional ethics to auditors performance but cannot be moderating between role ambiguity to auditors performance. While the coefficient of determination (R2) shows all the independent variable used in this study contributed 79.1% to the dependent variable while 20.9% were explaining other independent variable that are not obseved in this study.Keywords : Role, Sensitivity, Emotional and Auditors Performance.